1978
DOI: 10.1111/j.1365-2605.1978.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testicular and Ovarian Inhibin‐Like Activity, Using In Vitro and In Vivo Systems

Abstract: Inhibin‐like activities in charcoal‐treated bovine follicular fluid (FF) and medium from cultured Sertoli cells (SCCM) were assayed in an in vitro bioassay system, using cultured pituitary cells. Addition of both fluids resulted in parallel dose‐dependent decreases of the concentration of follicle‐stimulating hormone (FSH) in the medium, both in the presence or absence of luteinizing hormone‐releasing hormone (LH‐RH). A single injection of FF into immature and adult male and female rats resulted in decreased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…CSCCM causes significant suppression of LH and FSH at 2 and 3 hr but is not evident due to large standard error of the mean (SEM). De Jong et al [ 3 ] have screened porcine follicular fluid for inhibin activity using adult and prepubertal rats of either sex. De Jong et al [3] have observed specific suppression of circulating levels of FSH at 4 and 8 hr of injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCCM causes significant suppression of LH and FSH at 2 and 3 hr but is not evident due to large standard error of the mean (SEM). De Jong et al [ 3 ] have screened porcine follicular fluid for inhibin activity using adult and prepubertal rats of either sex. De Jong et al [3] have observed specific suppression of circulating levels of FSH at 4 and 8 hr of injection.…”
Section: Discussionmentioning
confidence: 99%
“…De Jong et al [ 3 ] have screened porcine follicular fluid for inhibin activity using adult and prepubertal rats of either sex. De Jong et al [3] have observed specific suppression of circulating levels of FSH at 4 and 8 hr of injection. Our inability to observe specific suppression of FSH may be due to differences in the source and potency of inhibin.…”
Section: Discussionmentioning
confidence: 99%
“…In bull calves between 4 and 10 wk of age, the increase in concentrations of FSH may induce formation or recruitment of its own receptors on the non-differentiated Sertoli cells (Smith and Ojeda, 1986). This recruitment of receptors for FSH could initiate biochemical changes within Sertoli cells, including mitosis, and prepare these cells for the onset of spermatogenesis (Griswold et al, 1976;deJong et al, 1978;Feig et al, 1980) when signalled by the second rise in plasma FSH observed between 12 and 20 wk of age. In the Holstein bull calf, Curtis and Amann (1981) observed that the numbers of Sertoli cells per testis began to increase sometime between 16 and 20 wk of age, soon after the age at which the second rise in plasma FSH was observed in the present study (Exp.…”
Section: ~--~---+--~R---+----r---+----~~~---+75mentioning
confidence: 99%
“…Factors that control the secretion of FSH prior to puberty are of considerable interest because FSH appears to be an important signal both to initiate growth and development of the gonad (Griswold et al, 1977;Solari and Fritz, 1978;Orth, 1984) and to stimulate the secretion of inhibin (INH) (Steinberger and Steinberger, 1976;deJong et al, 1978;Feig et al, 1980). The protein INH has been implicated in the control of FSH secretion in adult and prepubertal mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, nous avons montré (Blanc et al,1978;Cahoreau et al,1979) (Baker et al, 1976 ; Steinberger, 1976 ;Erickson et Hsueh, 1978 ;de Jong et al,1978de Jong et al, ,1979aLabrie et al, 1978 (Baker et al, 1976 ;Franchimont et al, 1978 ;de Jong et al, 1978 ;Labrie et al, 1978 ;Hudson et al, 1979) (Lugaro et ai., 1969(Lugaro et ai., , 1973(Lugaro et ai., , 1974 Dacheux, 1976 ;Baker et al, 1976Baker et al, ,1978Davies et al, 1976Davies et al, , 1978Franchimont et al, 1977Franchimont et al, , 1978 Franchimont, 1976 Main, 1977a ;humain : Franchimont et al, 1973humain : Franchimont et al, ,1975ahumain : Franchimont et al, , b, 1977humain : Franchimont et al, , 1978Thakur et al, 1978 ;Chari et al, 1979) Lugaro et al,1973 ; Demoulin, 1975a ;Baker et al, 1976 ;papaïne : Cahoreau et al, 1979) ou par les traitements thermiques supérieurs à 65 °C (Lugaro et al,1973 ;Baker et al,1976 ;Setchell, Davies et Main, 1977a ; (Vaughan, 1978). Cependant, l'arginine vasotocine ne modifie pas la sécrétion des gonadotropines de rat in vitro (Moskowska et Ebels, 1968 ;…”
Section: Introductionunclassified